Exploring Post-Fall Audit Report Data in an Acute Care Setting. (June 2015) - Tzeng, Huey-Ming; Yin, Chang-Yi
This retrospective, descriptive, chart review study was done to demonstrate one strategy for communicating aggregated and actionable fall data to bedside nurses. It was conducted at a nonprofit acute care hospital in the northwestern United States to analyze the quantitative data captured in post-fall audit reports of patient falls (March 1-December 31, 2012, N = 107 falls). Descriptive and binary statistical analyses were used. The quarterly National Database of Nursing Quality Indicators 2011 and 2012 reports showed that implementation of post-fall audit reports can lead to a lower overall fall rate and a lower fall-injury rate. Increased nursing hours could be a confounding factor of the positive impact of conducting post-fall audits in this study. It is concluded that timely and systematic reporting, analysis, and interpretation of fall data in an electronic format can facilitate prevention of falls and fall injuries.